Detection of the ABCB11930_1931del TC Mutation in Two Suspected Ivermectin-Sensitive Cats and Their Relatives by a Novel TaqMan Allelic Discrimination Assay - Nürnberger, Daniela; Wagner, Lisa; Müller, Simon F.; Leiting, Silke; Leidolf, Regina; Alber, Jörg; Hamann, Melanie; Geyer, Joachim (Frontiers in Veterinary Science, 2022)
The multidrug resistance gene MDR1 (syn. ABCB1) encodes for the multidrug efflux transporter P-glycoprotein (P-gp), which is highly expressed at the blood-brain barrier and protects the brain from potentially neurotoxic compounds, such as ivermectin. MDR1 mutation in dogs is known to be linked to dramatically increased brain accumulation of ivermectin and life-threatening neurological toxicity. The present report describes two suspected ivermectin-sensitive Maine Coon cats, which exhibited neurological toxicity following subcutaneous application of therapeutic doses of ivermectin. Both cats showed a homozygous 2-bp deletion in the MDR1/ABCB1 coding sequence (ABCB11930_1931del TC, syn. MDR1 nt1930(del2)) that had previously been associated with a drug-sensitive phenotype in cats. For cat MDR1 genotyping, a novel TaqMan allelic discrimination assay was established and validated. This assay was used for ABCB11930_1931del TC genotyping of the drug-sensitive cats as well as of more than 50 relatives. About half of them had the heterozygous MDR1(+/-) genotype, while none of these related cats with former ivermectin treatment had a history of drug-sensitivity. In conclusion: The present study supports previous findings on drug-sensitivity in cats with homozygous ABCB11930_1931del TC mutation. The newly established TaqMan allelic discrimination assay provides a useful and reliable method for routine MDR1 genotyping in cats in order to identify drug-sensitive cats prior to treatment with established P-gp substrates such as ivermectin and other macrocyclic lactones and thus to improve therapeutic safety.